Long run relationship between economic growth, export, population and investment of Ethiopia - Leta, M; Zemedkun, L (International Journal of Agricultural Research, Innovation and Technology, 2018)
The objective of this study is to examine the long-run relationship between economic growth, population, export, and investment in Ethiopia using annual data collected from the World development indicator, and FAOSTAT for 18 years from 1990-2007 E.C. Co integration and Granger Causality test. Stationary properties of the data and the order of integration of the data were tested using the Augmented Dickey-Fuller (ADF) test. Variables were non-stationary at levels but stationary in first differences. The long-run effects of Population, export and investment on Economic growth indicated that these variables are positively related to economic growth and statistically significant at 1% level. Int. J. Agril. Res. Innov. & Tech. 8 (2): 61-69, December, 2018